Healthcare Analytics Made Simple : Techniques in Healthcare Computing Using Machine Learning and Python. - Kumar, Vikas (Vik) (Packt Publishing Ltd, 2018)
Machine learning and analytics have been widely utilized across the healthcare sector of late. This book will bridge the gap between practicing doctors and you as a data scientist. You will learn how to work with healthcare data and gain better insight from this data to improve healthcare outcomes.